Prognostic Role of Residual Thrombus Burden Following Thrombectomy: Insights From the TOTAL Trial. (17th May 2022) - Alkhalil, Mohammad; Kuzemczak, Michał; Zhao, Robin; Kavvouras, Charalampos; Cantor, Warren J.; Overgaard, Christopher B.; Lavi, Shahar; Sharma, Vinoda; Chowdhary, Saqib; Stanković, Goran; Kedev, Saško; Bernat, Ivo; et al.
Abstract : Background: It is unclear whether more effective forms of thrombus removal than current aspiration catheters would lead to improved outcomes. We sought to evaluate the prognostic role of residual thrombus burden (rTB), after manual thrombectomy, in patients undergoing primary percutaneous coronary intervention with routine manual thrombectomy in the TOTAL trial (Thrombectomy Versus PCI Alone). Methods: This is a single-arm analysis of patients from the TOTAL trial who underwent routine manual aspiration thrombectomy. The rTB was quantified by an angiographic core laboratory using the Thrombolysis in Myocardial Infarction criteria and validated using existing optical coherent tomography data. Large rTB was defined as grade ≥3. The primary outcome was death from cardiovascular causes, recurrent myocardial infarction, cardiogenic shock, or new or worsening heart failure within 180 days. Results: Of 5033 patients randomized to routine thrombectomy, 2869 patients had quantifiable rTB (1014 [35%] had large rTB). Patients with large rTB were more likely to have hypertension, previous percutaneous coronary intervention, myocardial infarction, or Killip class III on presentation but less likely to have Killip class I. The primary outcome occurred more frequently in patients with large rTB, even after adjustment for known risk predictors (8.6% versus 4.6%; adjusted hazard ratio, 1.83 [95% CI, 1.34–2.48]). These patients also had a higher risk of cardiovascular death (adjusted hazard ratio, 1.83 [95% CI, 1.13–2.95]), cardiogenic shock (adjusted hazard ratio, 2.02 [95% CI, 1.08–3.76]), and heart failure (adjusted hazard ratio, 1.74 [95% CI, 1.02–2.96]) but not myocardial infarction or stroke. Conclusions: Large rTB is a common finding in primary percutaneous coronary intervention and is associated with increased risk of adverse cardiovascular outcomes, including cardiovascular death. Future technologies offering better thrombus removal than current devices may decrease or even eliminate the risk associated with rTB. This, potentially, can turn into a strategic option to be studied in clinical trials. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01149044.